1996
DOI: 10.1007/s004390050260
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent penetrance and mapping of the locus for juvenile and early-onset open-angle glaucoma on chromosome 1q (GLC1A) in a French family

Abstract: The GLC1A locus for autosomal dominant primary open-angle glaucoma (POAG) with juvenile onset (before 20 years) has been mapped to chromosome 1q21-q31. Recently, a French-Canadian family was described in which both juvenile-onset and middle-age or early-onset POAG were observed and linked to GLC1A. We now describe a second POAG family with variable age of onset (range 11-51, median 36 years of age). Linkage to GLC1A was established with a maximum lod score of 6.21 at the D1S452 locus. A recombination event in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…'6 17 These findings indicated that the range of phenotypes determined by the GLClA chromosomal region could be broader than initially thought. However, GLC1A was also probably excluded in one family with middle age onset OAG,'8 and a second localisation (GLCIB) on proximal chromosome 2q was recently proposed.…”
mentioning
confidence: 84%
“…'6 17 These findings indicated that the range of phenotypes determined by the GLClA chromosomal region could be broader than initially thought. However, GLC1A was also probably excluded in one family with middle age onset OAG,'8 and a second localisation (GLCIB) on proximal chromosome 2q was recently proposed.…”
mentioning
confidence: 84%
“…Therefore, very likely, this patient, who was also born in Western France, had inherited the same mutation. (Sheffield et al, 1993;Meyer et al, 1996;Brezin et al, 1998). Identifying these subjects and screening their relatives for mutations should help to prevent irreversible glaucomatous lesions of optic nerves in carriers, since efficient therapies are already available.…”
Section: Allelic Associations With Myoc Mutations Denote Founding Effmentioning
confidence: 99%
“…In addition to the differences in angle morphology, the age of onset of glaucoma varies from juvenile to adult onset in the families linked to 1q21-31 Sheffield et al 1993;Richards et al 1994;Wiggs et al 1994;Graff et al 1995;Morisette et al 1995;Meyer et al 1996). Hence, another explanation for the discrepant clin-133 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dysgenesis of the iridocorneal angle has been reported in one ADJG family linked to the GLC1A locus on chromosome 1q21-31 (Graff et al 1995) but not in others Sheffield et al 1993;Richards et al 1994;Wiggs et al 1994Wiggs et al , 1995Morisette et al 1995;Meyer et al 1996). The adult-onset normal tension open-angle glaucoma family linked to chromosome 2cen-q13 was not reported to have any angle malformations (Stoilova et al 1996).…”
Section: Introductionmentioning
confidence: 99%